1998
DOI: 10.1046/j.1365-313x.1998.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of PHYA in wild‐type and phytochrome A‐deficient mutants of tomato

Abstract: SummaryTomato (Lycopersicon esculentum Mill., recently redesignated Solanum lycopersicum L.), an agronomically important crop plant, has been adopted as a model species complementary to Arabidopsis in which to characterize the phytochrome family. Here we describe the cloning and molecular characterization of the gene encoding the apoprotein of phytochrome A in wild-type tomato and in the far-red-light-insensitive (fri 1 and fri 2 ) tomato mutants. The physical organization of this gene is similar to that of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Nor does convincing evidence exist to indicate that phyA regulates light-induced lycopene accumulation in these fruit. Preliminary results obtained in our laboratory (data not shown) indicate, however, that neither red nor red/far-red-light treatments influence the pigmentation of fruit obtained from a phyA Ϫ mutant (cv MoneyMaker; Lazarova et al, 1998a). These initial data are consistent with the hypothesis that fruitlocalized phyA participates in light-induced lycopene accumulation in tomato fruit.…”
Section: Fruit-localized Phytochromes Regulate Lycopene Accumulation supporting
confidence: 76%
See 1 more Smart Citation
“…Nor does convincing evidence exist to indicate that phyA regulates light-induced lycopene accumulation in these fruit. Preliminary results obtained in our laboratory (data not shown) indicate, however, that neither red nor red/far-red-light treatments influence the pigmentation of fruit obtained from a phyA Ϫ mutant (cv MoneyMaker; Lazarova et al, 1998a). These initial data are consistent with the hypothesis that fruitlocalized phyA participates in light-induced lycopene accumulation in tomato fruit.…”
Section: Fruit-localized Phytochromes Regulate Lycopene Accumulation supporting
confidence: 76%
“…Taken together, the data of Hauser et al (1997) and those presented here raise the possibility that pigmentation of these fruit (and possibly other processes of fruit ripening) might be influenced by multiple phytochromes, perhaps in response to different illumination conditions. Future investigations with the available phyA (Lazarova et al, 1998a), phyB1 (Lazarova et al, 1998b), and phyB2 (Kerckhoffs et al, 1999) mutants should provide insights into the specific roles of these three phytochromes in tomato ripening.…”
Section: Fruit-localized Phytochromes Regulate Lycopene Accumulation mentioning
confidence: 99%
“…In the cop1-6 mutant of the Arabidopsis COP1 locus, an A-to-G mutation at −2 of intron 4 converting AG/ to GG/ activates cryptic canonical AG/ splice sites at significant distances upstream (−15, −37) and downstream (+16) of the normal 3′ splice site position (McNellis et al 1994). In the fri mutants of the tomato PHYA locus, an A-to-U mutation at this same position of intron 1 converting AG/ to UG/ leads to intron retention and activation of cryptic canonical 3′ splice sites upstream (−53, −81) and downstream (+6, +21, +99) of the normal 3′ cleavage site as well as the rare usage of the noncanonical UG/ at the normal 3′ cleavage site and, occasionally, exon skipping (Lazarova et al 1998). In the cop1-1 mutant, a G-to-A mutation at −4 of intron 5 converting the optimal CGCAG/ U 3′ splice site to CACAG/ U primarily causes skipping of downstream exon 6 and secondarily activates a cryptic 5′ splice site in intron 6 that is 46 nucleotides downstream of the normal 5′ splice site (Simpson et al 1998).…”
Section: Natural and Chemically Induced Splice Site Mutationsmentioning
confidence: 99%
“…A single Arabidopsis gene, PHYA, encodes a light-labile type I phytochrome, which has been shown through mutant analysis to function in very low fluence and FR high irradiance responses (Shinomura et al, 1996;Hamazato et al, 1997;Whitelam and Devlin, 1997). Mutations in PHYA genes from tomato, pea (Pisum sativum), and rice (Oryza sativa) result in similar defects in these general classes of phytochrome responses (Weller et al, 1997;Lazarova et al, 1998a;Takano et al, 2001). Somers et al (1991) showed that the Arabidopsis PHYB and PHYC genes encode proteins that are less abundant than phyA in etiolated tissue and appear to be light stable.…”
mentioning
confidence: 99%